Antibacterial UV-photocured acrylic coatings containing quaternary ammonium salt - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (SPRINGER, 2021)
This study aimed to develop UV-curable coating materials showing antimicrobial properties. GTAC was acrylated and characterized by FT-IR and(1)H NMR spectroscopy. UV-curable coating materials with different contents were prepared. Inhibition zone method was used to determine the antimicrobial activity of the materials. Thermal stability of samples was evaluated by TGA. Contact angles of samples were measured to obtain information about their hydrophobicity. Surface morphology of samples was investigated by SEM. Produced UV-curable coating materials have good antimicrobial, thermal and surface properties, and they can be used as antibacterial top coating material in many industries.
Keywords: Antimicrobial; UV curable; Coating; Nanoparticles; SILVER; ADDITIVES; COPPER